Branding Usaha Produk Pengkilat Ban “ Bagged “ - Aditya, Fendra; Tanjung, Muhammad Rusdi; Aryandi, Mirda; Pratama, Randi; Girsang, Nitasri Murawaty (INSTITUT SENI INDONESIA PADANGPANJANG, 2024)
The branding carried out on the tire shine product business owned by Mrs. Agustina Lubis aims to increase sales figures for one of the tire shine products. In creating the product branding, the creation method used is preparation, elaboration, synthetic/pre-production, Mind Mapping/Brainstorming, Realization/production, and Completion/post-production. Now the product can be sold and marketed from what was initially only sold to regular customers and to car wash businesses around the house or the city of Binjai. Now the sales reach can be even wider through online media which of course makes the product better known and recognized by new consumers because it already has a clear brand name or brand to provide a sense of consumer trust regarding the quality of the products they buy. With the new packaging or packaging, the tire shine product can now be marketed more safely, much better and finally the product itself can also be used directly more easily for consumers.Keywords : Branding, Tire Shine, Promotion Strategy